Incorporating Heavy Alkanes in Metal–Organic Frameworks for Optimizing Adsorbed Natural Gas Capacity. Issue 64 (26th October 2018) - Fang, Yu; Banerjee, Sayan; Joseph, Elizabeth A.; Day, Gregory S.; Bosch, Mathieu; Li, Jialuo; Wang, Qi; Drake, Hannah; Ozdemir, Osman K.; Ornstein, Jason M.; Wang, Ye; Lu, Tong‐Bu; et al.
Abstract: Metal–organic frameworks (MOFs) as methane adsorbents are highly promising materials for applications such as methane‐powered vehicles, flare gas capture, and field natural gas separation. Pre‐ and post‐synthetic modification of MOFs have been known to help improve both the overall methane uptake as well as the working capacity. Here, a post‐synthetic modification strategy to non‐covalently modify MOF adsorbents for the enhancement of the natural gas uptake for the MOF material is introduced. In this study, PCN‐250 adsorbents were doped with C10 alkane and C14 fatty acid and their impact on the methane uptake capabilities was investigated. It was found that even trace amounts of heavy hydrocarbons could considerably enhance the raw methane uptake of the MOF while still being regenerable. The doped hydrocarbons are presumably located at the mesoporous defects of PCN‐250, thus optimizing the framework–methane interactions. These findings reveal a general approach that can be used to modify the MOF absorbents, improving their ability to be sustainable and renewable natural gas adsorption platforms. Abstract : A non‐covalently modified mesoporous metal–organic framework (MOF) with long‐chain hydrocarbons could significantly increase the already high methane uptake. The long‐chain fatty acid was assumed to be coordinated to the open metal site and located at the mesoporous defects of the MOF. Through optimized partitioning of the mesoporous space of MOF by the doped hydrocarbons, more methane was packed into the pores of the MOF through hydrophobic interactions.